Aging Gracefully in the Renaissance - Stories of Later Life from Petrarch to Montaigne - Skenazi, Cynthia (Medieval and Renaissance Authors and Texts, 2013)
Cynthia Skenazi explores in this book a shift in attitudes towards aging and provides a historical perspective on a crucial problem of our time. In Aging Gracefully in the Renaissance: Stories of Later Life from Petrarch to Montaigne Cynthia Skenazi explores a shift in attitudes towards aging and provides a historical perspective on a crucial problem of our time. From the late fourteenth to the end of the sixteenth centuries, the elderly subject became a point of new social, medical, political, and literary attention on both sides of the Alps. A movement of secularization tended to dissociate old age from the Christian preparation for death, re-orienting the concept of aging around pragmatic matters such as health care, intergenerational relationships, and accrued insights one might wish to pass along. Such changes were accompanied by an increasing number of personal accounts of later life. This title was made Open Access by libraries from around the world through Knowledge Unlatched.